Optimal Placement and Sizing of DSTATCOM Using Harmony Search Algorithm. (November 2015) - Yuvaraj, T.; Devabalaji, K.R.; Ravi, K.
Abstract: This paper investigates a new approach to find the optimal location and sizing of Distribution STATic COMpensator (DSTATCOM) with an objective function of minimizing the total network power losses. Harmony search algorithm is used to find the optimal location and sizing of DSTATCOM. The proposed work is tested on standard IEEE 33-bus radial distribution systems. The obtained result shows that optimal placement and sizing of DSTATCOM in the radial distribution network effectively reduces the total power losses of the system.